Use of Tofacitinib for the Treatment of Arthritis Associated With Ulcerative Colitis. Issue 9 (September 2019) - Wang, Wenfei; Cleveland, Noa Krugliak; Ollech, Jacob; Rubin, David T.
Abstract : ABSTRACT: Tofacitinib is a Janus kinase 1–3 inhibitor initially approved for the treatment of rheumatoid arthritis and now approved for the treatment of moderately to severely active ulcerative colitis (UC). We present the case of a patient with UC and seronegative inflammatory arthritis in whom arthritis progressed while on vedolizumab and was successfully treated with tofacitinib. This case provides insight into the use of tofacitinib for the treatment of UC and a concomitant extraintestinal manifestation of joint involvement.